Sistem Pendeteksi Kekeruhan Air Pada Bioflok Ikan Lele di Desa Bulontala Timur - Asri, Muhammad; Hulukati, Stephan A.; Nyaman, Fazal S. (Jurnal Ilmiah Ilmu Komputer Banthayo Lo Komputer, 2023)
Abstract-The purpose of this research is to build a water turbidity detection tool in Arduino Uno-based catfish bioflocs. Catfish cultivation managed by the Al-Hidayah Farmer group in East Bulontala Village is recommended to pay attention to the turbidity of the water in the catfish pond because of the large number of particles and suspended substances in the pond water that can cause catfish growth to be inhibited. The construction of a water turbidity detection device in catfish Bioflocs is expected to improve catfish growth. This research focuses on six samples of catfish pond water with three states of pond water turbidity. Testing is done by giving input to the tool and the resulting output can display turbidity information data through the LCD. From the measurement results of the water turbidity detection device on the catfish biofloc, it is concluded that if the turbidity of the catfish pond water is less than 20 NTU, the pond water is declared clear. Then if the turbidity of the catfish pond water is more than 20 to less than 50 NTU, the pond water is declared in a moderate state. On the other hand, if the turbidity of the catfish pond water is more than 50 NTU, the catfish pond water is declared turbid. The tool that has been designed can function and provide information about the water quality of the biofloc system catfish pond where the water quality of the pond in the Al-Hidayah Farmer group in East Bulontala Village is still relatively good in accordance with the standardization of water quality for fish. Keywords: Bioflok; water turbidity; turbidity sensor